The budget system of the Republic of Kazakhstan. (Journal of actual problems of jurisprudence, 2016)
In this article, the author has considered the theoretical and practical problems relating to the budget system of the Republic of Kazakhstan. In the study were considered the Constitution of the Republic of Kazakhstan, the Budget Code of the Republic of Kazakhstan and other regulatory legal acts. Also, in order to reveal the topics are covered principles of the budget system of the Republic of Kazakhstan. Budgetary matters disclosed relevance to society. The process offormation of republican and local budgets in RK is investigated.
Keywords: Budget system; local budget; republican budget; mandatory payments